PENANGANAN KRISIS PENGUNGSI KONFLIK ETHIOPIA-TIGRAY OLEH UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES (UNHCR) - Dwivinanti, Lulu; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Back in 2020, there was a civil war between the Federal government of Ethiopia and the Tigray People's Liberation Front (TPLF) that led to a six-month state of emergency. The crux of the conflict lies in different political ideologies. UNHCR provides humanitarian assistance, protection, and coordination with the main target of internally displaced persons (IDPs) in Ethiopia. The author uses qualitative research methods and employs Clive Archer's theory of the role of international organisations to assess how the United Nations High Commissioner for Refugees (UNHCR) handled the internally displaced persons (IDPs) in the Ethiopia-Tigray conflict. The findings of this study show that UNHCR actively carries out its role as an international organisation in handling internally displaced persons affected by the Ethiopia-Tigray conflict as actors. UNHCR directly uses its implementation on most of the aid activities for IDPs. UNHCR not only serves as an ally to UN states, but also develops and implements prevention strategies and solutions to internal crises, addressing challenges such as unstable food conditions and limited resources. UNHCR prioritises meeting the needs of internally displaced Ethiopians by moving shelters, delivering Core Relief Items (CRIs), and providing humanitarian assistance, which includes daily living needs such as non-food items. UNHCR has final responsibility in its role as an operational actor, directly utilising its implementation on most relief activities for IDPs in the Ethiopia-Tigray conflict. Keywords: UNHCR, Ethiopia-Tigray Conflict, Internally Displaced Person (IDPs)